Determination of the proportion of severe impairment of the upper extremity functions in patients with chronic stroke - Wanpen, Sawitri; Hla Tun, Su Sandi; Nualnetr, Nomjit; Chatchawan, Uraiwan; Puntumetakul, Rungthip (Asia-Pacific Journal of Science and Technology, 2025)
The objective of this study was to assess the proportion of upper extremity (UE) motor impairment and activity limitation in Myanmar individuals with chronic stroke and to find out the correlation between motor impairment and activity limitation. The research was conducted at North Okkalapa General Hospital, Yangon, Myanmar. The motor portion of Fugl-Meyer Assessment-Upper Extremity (FMA-UE) and Streamlined Wolf Motor Function Test for chronic stroke (SWMFT-C) were applied to assess the UE motor impairment and activity limitation. The result showed that 38 patients with chronic stroke were impaired in their UE functions (FMA-UE score of 7.0-52.0). Among these, four levels of impairments were demonstrated with full impairment (31.6%), severe impairment (15.8%), moderate impairment (50%), and mild impairment (2.6%). For the UE activities, the mean score (SD) of SWMFT-C performance time (s) was 7.52 seconds (6.00). The mean score (SD) of SWMFT-C functional ability scale (SWMFT-C-FAS) was 2.70 (1.12). In conclusion, the majority of the patients with chronic stroke were with moderate and severe motor impairment and activity limitation in their UE. Therefore, UE rehabilitation is needed to improve the impairments and functional recovery.